THE INFLUENCE OF GIMKIT INNOVATIVE LEARNING MEDIA ON STUDENT LEARNING OUTCOME - Andriana, Encep; Ruhiyat, Yayat; Nulhakim, Lukman (Universitas Negeri Semarang, 2024)
Seeing that there are still many teachers who find it difficult to create innovative learning, especially using technology as learning in accordance with the times of today's students. So this study was conducted with the aim of knowing the effect of using innovative learning media using the Gimkit website on learning outcomes, the learning outcomes obtained are attitudinal learning outcomes and scores. This research was conducted at SD Tirtayasa with 60 grade 5 students who participated in Gimkit innovative learning. The research itself used a quantitative approach and descriptive method to obtain and present the research results. From the results of this study, it is concluded that technology-based innovative learning affects the learning outcomes of students' attitudes and values, and in this study both obtained good results. So from this research, the hope is that teachers have a reference or alternative to try and explore providing innovative learning through Gimkit.